A Csanádi Egyházmegye Mária-ünnepe, 1948 = Mary's festival of the Csanád diocese, 1948 - Medgyesi Konstantin (Belvedere Meridionale Szeged, 2024)
The Diocese of Csanád’s Mary’s Day, held on 22-23 May 1948, became one of the largest mass events ever held in the diocese and the city of Makó. Different sources give different estimates of the number of participants, but it is certain that tens of thousands of people attended the event. Seven years before the arrest of Cardinal József Mindszenty, the event was a silent protest against the emerging communist dictatorship.
Keywords: Bölcsészettudományok; Történettudomány és régészet